Time-restricted feeding during childhood has persistent effects on mice commensal microbiota - Hu, Dandan (Ann Transl Med, 2019)
BACKGROUND: Time-restricted feeding (TRF) has been proved to improve general health in adults. However, according to our previous study, this regimen failed to show similar protective effect in pediatric population. Gut microbiota has been proved to play a vital part in the whole process. Although previous studies have defined the commensal flora as a real-time indicator of health conditions in adults, our study aimed to investigate whether the unfavorable TRF feeding schedule during childhood would cause long-term variations in murine model. METHODS: We randomly assigned 120 4-week-old Kunming mice (half male and half female) to four feeding regimens: TRF.AD, time-restricted feeding during the childhood phase before switched to ad libitum feeding pattern as adults; TRF.TRF, continuously treated with time-restricted feeding; AD.TRF, went through time-restricted feeding only in adulthood; AD.AD, always had ad libitum access to food. After 8 weeks of dietary intervention, faeces were harvested from 12-week-old adult mice (one subject per cage), and gut microbiota was subsequently analysed via DNA extraction and 16s rRNA sequencing. RESULTS: Mice on identical diet for four weeks but went through different feeding patterns during childhood showed distinctive traits in gut microbiota. Differences existed in both the α diversity and specific groups of bacteria under different taxonomical levels. CONCLUSIONS: Feeding pattern in the childhood had long-term impact on mice gut flora that cannot be wiped out in adulthood.